Redmap Australia: Challenges and Successes With a Large-Scale Citizen Science-Based Approach to Ecological Monitoring and Community Engagement on Climate Change - Pecl, Gretta T.; Stuart-Smith, Jemina; Walsh, Peter; Bray, Dianne J.; Kusetic, Martha; Burgess, Michael; Frusher, Stewart D.; Gledhill, Daniel C.; George, Oliver; Jackson, Gary; Keane, John; Martin, Victoria Y.; et al. (Frontiers in Marine Science, 2019)
Citizen science includes a suite of research approaches that involves participation by citizens, who are not usually trained scientists, in scientific projects. Citizen science projects have the capacity to record observations of species with high precision and accuracy, offering the potential for collection of biological data to support a diversity of research investigations. Moreover, via the involvement of project participants, these projects have the potential to engage the public on scientific issues and to possibly contribute to changes in community knowledge, attitudes and behaviours. However, there are considerable challenges in ensuring that large-scale collection and verification of species data by the untrained public is a robust and useful long-term endeavor, and that project participants are indeed engaged and acquiring knowledge. Here, we describe approaches taken to overcome challenges in creation and maintenance of a website-based national citizen science initiative where fishers, divers, and other coastal users submit opportunistic photographic observations of ‘out-of-range’ species. The Range Extension Database and Mapping Project (Redmap Australia) has two objectives, 1/ ecological monitoring for the early detection of species that may be extending their geographic distribution due to environmental change, and 2/ engaging the public on the ecological impacts of climate change, using the public’s own data. Semi-automated ‘managed crowd-sourcing’ of an Australia-wide network of scientists with taxonomic expertise is used to verify every photographic observation. This unique system is supported by efficient workflows that ensures the rigor of data submitted. Moreover, ease of involvement for participants and prompt personal feedback has contributed to generating and maintaining ongoing interest. The design of Redmap Australia allows co-creation of knowledge with the community - without participants requiring formal training - providing an opportunity to engage sectors of the community that may not necessarily be willing to undergo training or otherwise be formally involved or engaged in citizen science. Given that capturing changes in our natural environment requires many observations spread over time and space, identifying factors and processes that support large-scale citizen science monitoring projects is increasingly critical.